The dangers of ionizing radiation that affect human safety and the environment :A review Article (Texas Journal of Medical Science, 2023)
The world is witnessing an increase in the spread of nuclear technology and the expansion of the use of radionuclide in industry, agriculture, medicine and other nuclear and radiological applications. This may be accompanied by an increase in accidents as the threat of potential risks from human exposure increases externally exposed to ionizing radiation and contamination of its internal organs with radionuclide. In order to protect people and workers from health harms associated with external exposure for ionizing radiation and indoor contamination with radionuclides, follow the principles of health prevention and control implementing rules and laws for the protection of ionizing radiation that ensure safety for humans and the environment reducing radiation risks.